A Novel MCPH1 Isoform Complements the Defective Chromosome Condensation of Human MCPH1-Deficient Cells - Gavvovidis, Ioannis (Public Library of Science, 2012)
Biallelic mutations in MCPH1 cause primary microcephaly (MCPH) with the cellular phenotype of defective chromosome condensation. MCPH1 encodes a multifunctional protein that notably is involved in brain development, regulation of chromosome condensation, and DNA damage response. In the present studies, we detected that MCPH1 encodes several distinct transcripts, including two major forms: full-length MCPH1 (MCPH1-FL) and a second transcript lacking the six 3′ exons (MCPH1Δe9–14). Both variants show comparable tissue-specific expression patterns, demonstrate nuclear localization that is mediated independently via separate NLS motifs, and are more abundant in certain fetal than adult organs. In addition, the expression of either isoform complements the chromosome condensation defect found in genetically MCPH1-deficient or MCPH1 siRNA-depleted cells, demonstrating a redundancy of both MCPH1 isoforms for the regulation of chromosome condensation. Strikingly however, both transcripts are regulated antagonistically during cell-cycle progression and there are functional differences between the isoforms with regard to the DNA damage response; MCPH1-FL localizes to phosphorylated H2AX repair foci following ionizing irradiation, while MCPH1Δe9–14 was evenly distributed in the nucleus. In summary, our results demonstrate here that MCPH1 encodes different isoforms that are differentially regulated at the transcript level and have different functions at the protein level.